2011
DOI: 10.1080/1745039x.2010.520408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded levels of rare earth elements in diets of fattening bulls on growing and slaughtering performance, and on nutrient digestibility of wethers

Abstract: The aim of the present dose response study was to examine the long-term effects of increasing the amounts of rare earth elements (REE) in the diet on growth and slaughtering performance of fattening bulls. A total of 48 bulls of German Holstein with an average initial live weight (LW) of 119 + 13 kg were divided into four dietary treatment groups (n = 12): a control group and three REE-treated groups, which were fed a supplement of 100, 200 and 300 mg REE-citrate per kg dry matter (DM) containing mainly cerium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The quadratic response to REE addition indicated that 300 mg/kg DM did not increase nutrient digestibility in the total tract and in situ ruminal ED of Leymus chinensis aNDF. This observation was in accordance with Schwabe et al (2011), who observed no significant influence on digestibility of nutrients by addition of 300 mg/kg DM REE.…”
Section: Effect Of Rare Earth Elements In Sheepsupporting
confidence: 79%
“…The quadratic response to REE addition indicated that 300 mg/kg DM did not increase nutrient digestibility in the total tract and in situ ruminal ED of Leymus chinensis aNDF. This observation was in accordance with Schwabe et al (2011), who observed no significant influence on digestibility of nutrients by addition of 300 mg/kg DM REE.…”
Section: Effect Of Rare Earth Elements In Sheepsupporting
confidence: 79%
“…Apart from the intense industrial use, REEs are applied in Chinese agriculture for over four decades. Positive effects in plant production and animal husbandry have been documented (He et al 2001;Schwabe et al 2011;Hu et al 2004). Hu et al (2006) summarized that in China in 2001 6.5 million ha of land were treated with 11,000 t of REEs by direct application of microelement fertilizers.…”
Section: Introductionmentioning
confidence: 96%
“…The reason for the differences in the results between different trials could be that the REE levels used in the trials of Schwabe et al. () were lower than in other trials. The results indicated that the effects of REE on increasing nutrient digestibility could be dose dependent.…”
Section: Discussionmentioning
confidence: 86%
“…Schwabe et al. (), however, reported that supplementing up to 300 mg REE citrate/kg DM to the rations of growing and fattening cattle, consisting of 25.3% REE or 38.7% REE, respectively (REE composition: 57.9% Ce, 34.0% La, 6.5% Pr and 1.6% other REE), did not affect the digestibility of CP, NDF or ADF. The reason for the differences in the results between different trials could be that the REE levels used in the trials of Schwabe et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation